TPPS supported on core–shell PMMA nanoparticles: the development of continuous-flow membrane-mediated electrocoagulation as a photocatalyst processing method in aqueous media12. Issue 3 (2nd February 2015) - Dambruoso, Paolo; Ballestri, Marco; Ferroni, Claudia; Guerrini, Andrea; Sotgiu, Giovanna; Varchi, Greta; Massi, Alessandro
Abstract : Photons and electrons cooperate for effective, clean sulfoxidations in pure water. Abstract : Herein, the successful utilization of core shell poly-methyl methacrylate nanoparticles (CS-PMMA NPs) as a valuable support for organocatalyst immobilization in aqueous medium is presented along with an unprecedented direct current-based electrochemical method for processing a water colloid of the resulting nano-supported catalyst. The NP coagulation procedure relied on various electrocoagulation techniques and it was achieved through water electrolysis occurring in a dialysis membrane immersed in the colloid. Mass recoveries of up to 95% w/w were obtained for the NPs within 1 h of electrolysis. This was optimized at a constant current of 90 mA or a constant potential of 24 V. The disclosed NP separation procedure was effectively exploited in a continuous-flow reaction/separation/recycle sequence involving the tetraphenylporphyrin tetrasulfonate (TPPS) organo-photocatalyst immobilized on CS-PMMA NPs (NP2s ). After an optimization study aimed at maximizing the chemical efficiency of the entire synthetic and purification process, the nano-supported catalystNP2 (0.05 mol%) efficiently promoted the photoexcitation of triplet oxygen to singlet oxygen for the selective and environmentally benign sulfoxidation of a model sulfide in an aqueous medium.